2019
DOI: 10.1142/s0217984919502658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaF additive on the micro/nano-structure and properties of the microarc oxidation coating on Ti6Al4V alloy

Abstract: Micro/nano-structured coatings with antibacterial function were prepared by microarc oxidation (MAO) treatment on Ti6Al4V alloy in a silicate/phosphate electrolyte with a NaF additive. The microstructure, phase composition, and corrosion resistance of the coatings modified by adding NaF (0.15–0.5 M) were examined using scanning/transmission electron microscopy, energy dispersive spectroscopy, atomic force microscopy, X-ray diffraction, and potentiodynamic polarization. The results showed that the incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Tsuchiya et al (2006) showed that lower pH values on fluoride media promote competition between the growth and dissolution of the oxide film, allowing nanotube shaped oxides to be formed. Zhai et al (2019) argue that titanium and its alloys present good mechanical properties as well as good biocompatibility, but they have no Research, Society and Development, v. 9, n. 11, e95791110689, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.10689…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsuchiya et al (2006) showed that lower pH values on fluoride media promote competition between the growth and dissolution of the oxide film, allowing nanotube shaped oxides to be formed. Zhai et al (2019) argue that titanium and its alloys present good mechanical properties as well as good biocompatibility, but they have no Research, Society and Development, v. 9, n. 11, e95791110689, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.10689…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been used in studies about optical parameters, oxide layer thickness related to electrochemical behaviour of titanium and its alloys, mainly in acidic or alkaline environments (Mardare & Hones, 1999;Blackwood et al, 1989). Atomic force microscopy (AFM) is a well-known and widely used technique to investigate the roughness and surface topography of the samples (Saldanha et al, 2020;Huang & Liu, 2013;Zhai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%